Terbium sisters: current development status and upscaling opportunities - Moiseeva, Anzhelika N.; Favaretto, Chiara; Talip, Zeynep; Grundler, Pascal V.; van der Meulen, Nicholas P. (Frontiers in Nuclear Medicine, 2024)
The interest in terbium radionuclides, which can be used in nuclear medicine, has increased tremendously over the last decade. Several research studies have shown the potential of four terbium radionuclides 149,152,155,161 Tb both for cancer diagnosis as well as therapy. The comparison of 161 Tb and 177 Lu showed 161 Tb as the preferred candidate not only for standard radiotherapy, but also for the treatment of minimal residual disease. Nevertheless, among the terbium sisters, currently, only 161 Tb has an established production protocol where its no-carrier-added form is obtained via neutron irradiation of enriched 160 Gd targets. The other terbium radioisotopes face challenges related to production capacity and production yield, which currently restricts their use in nuclear medicine. The purpose of this review is to report on recent research on the production and separation of terbium sisters and to assess the prospects for upscaling their production for nuclear medicine applications.